Morphology, palynology, and stipe anatomy of four common ferns from Pekanbaru, Riau Province, Indonesia - NERY SOFIYANTI; DYAH IRIANI; FITMAWATI FITMAWATI; AFNI ATIKA MARPAUNG (Society for Indonesian Biodiversity, 2019)
Sofiyanti N, Iriani D, Fitmawati, Marpaung AA. 2019. Morphology, palynology, and stipe anatomy of four common ferns from Pekanbaru, Riau Province, Indonesia. Biodiversitas 20: 327-336. The fern explorations had been conducted in Pekanbaru, Riau Province from 2013 to 2017. The objectives of this study were to characterize the morphological characters, to examine the spore features and stipe anatomy characters of four common ferns from Pekanbaru. The specimens were collected from the fields using the exploration method from 21 study sites from 10 sub-districts. The spores were then observed using a digital microscope. A total of four fern species were known as the most common fern species in this region, i.e., Dicranopteris linearis, Stenochlaena palustris, Nephrolepis biserrata, and Davalia denticulata. This study examined the morphology, palynology and stipe anatomy of these four common ferns from Pekanbaru, Riau. The anatomical preparation was conducted using paraffin method while spore preparation using acetolysis method. We found dimorphic ferns (Stenochlaena palustris and Davallia denticulata) and monomorphic ferns (Dicranopteris linearis and Nephrolepis biserrata). The vascular bundle of stipes of four species examined is similar, i.e., amphicribral concentric, however, the vascular bundles within the species varies in size. We also observed similar type of stele, atactostele, among the species. The spore features found in this study were monolete and trilete with prolate and subprolate shape. The result of this study supports the anatomical data of the examined species.